Agriculture practiced by city dwellers and the urbanization process: an analysis on the european context - Pereira, Claudinei Silva [UNESP]; Hespanhol, Antonio Nivaldo [UNESP] (Univ Federal Goias, Inst Estudos Socio-ambientais, 2024)
The cultivation of food in urban space has been a common practice since the beginning of cities, when the technical and social division of labor was elementary. The production of food in backyards and near people's homes was an important factor in food security. After the First Industrial Revolution, disputes over the use of urban space was intensified, with the subsequent reduction of the importance of food cultivation in the cities. This article main purpose is to provide an understanding of the agriculture practiced in cities and their surroundings in the European context, in order to understand their purposes and relations with the labor market and food supply over time. Changes resulting from the expansion of the urbanization process are evident, as well as the existing relationships between agriculture and urban morphology. The structural transformations of the capitalist economy, starting in the 19th century, culminated in the reduction or disappearance of urban agriculture in certain areas of the main European cities, resulting in the constitution of a specialized food market, whose supply is carried out by merchants who purchase food produced in areas that are increasingly distant from the final consumer.
Keywords: Urban agriculture; Food security; Urban morphology